Considerations about aging and quality of live - Asunción Ors Montenegro; Ana Laguna Pérez (Universidad de Alicante, 1997)
The way one ages is always personal. It is the result of one's own genetic load together with his/her adaptation to the life stage. A satisfactory adaptation, self-respect, freedom, happiness and wellbeing, bear a strong relationship to the quality of life in general terms. Factors we consider essential for good quality of life in old age (elderly) are: physical, psychical and social fitness; a long and happy partnership with a loved-one, and self-perception of the state of one's health. A good financial situation in old age, could sometimes be less significant, if compared with their former times in life when they have lived with more limited resources. It is not so important either when there is a social support such as NHS and/or certain bonuses which guaranty satisfaction for their basic needs such as food, clothing and housing for life.